IoT-based System for Covid-19 Indoor Safety Monitoring - Mohd Ali, Nazurah; Suriani, Nor Surayahani (Evolution in Electrical and Electronic Engineering, 2021)
The world is now facing a deadly pandemic named COVID-19. Although there are existing touchless thermometer and automatic sanitizer everywhere during this pandemic season that hit our country even the whole world.Therefore, this project aims to design an IoT based COVID-19 health monitoring system based on body temperature, sanitizing system, and air quality control.This Indoor Safety Monitoring system focusing on the entrance of the small room by displaying the reading of the body temperature and air quality at the moment.The overall system is working automatically by sensing the temperature, distance and existence of smoke. This signal will be processed by Arduino UNO as the microcontroller and send to the cloud. Users get the notification from BLYNK application that can be downloaded for Android and iOS user. The objectives of this project are achieved.